People out of place : globalization, human rights, and the citizenship gap - Brysk, Alison, 1960-; Shafir, Gershon (Routledge, 2004)
"Globalization pushes people "out of place"--Across borders, out of traditions, into markets, and away from the rights of national citizenship. But globalization also contributes to the spread of international human rights ideas and institutions. This book analyzes the impact of these contradictory trends, with a focus on vulnerable groups such as migrants, laborers, women, and children. Theoretical essays by Richard Falk, Ronnie Lipschutz, Aihwa Ong, and Saskia Sassen rethink the shifting nature of citizenship. This collection advances the debate on globalization, human rights, and the meaning of citizenship."--pub